Engaging Students in a Research Methods Writing Lab Online. (January 2021) - Rice, Lindsay; Alquist, Jessica L.; Penuliar, Michael; Donato, Francesco V.; Price, Mindi M.
Courses including lab- or experiential-based learning may shy away from an online lab format. Using an empirically driven approach, an online research methods in psychology lab section was developed and compared to a face-to-face lab section. Results indicated that there were no differences in student knowledge regarding the American Psychological Association style and in the quality of the term papers (as evaluated by independent coders). Although students did not know whether they would be in a face-to-face or online lab when they enrolled, at the end of the semester, students expressed a preference for the style of lab in which they were enrolled. Recommendations for presenting labs or experiential learning content in an online format are discussed.